Effects of gradient density on effective heat capacity of charring ablative material for re-entry vehicles. Issue 3 (7th April 2015) - Li, Weijie; Huang, Haiming; Yu, Hailing; Xu, Xiaoliang
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The effective heat capacity is a key index to estimate the thermal protection performance of charring ablative materials in reentry vehicles subjected to aerodynamic heat loads. The purpose of this paper is to investigate the effects of gradient density on the effective heat capacity. Design/methodology/approach – Based on the Fourier law and the pyrolysis interface model, the authors establish the governing equations for the transient heat conduction with variable density, and then simulate one-dimensional transient thermal behavior of a homogeneous and three types of non-homogeneous charring ablative material in reentry capsules by using the implicit numerical method. Findings – The moving rate of pyrolysis interface and the surface temperature of charring ablative material depend on not only the surface heating history, but also the gradient density. And the gradient density can improve the insulation performance of charring materials, e.g. the effective heat capacity in the bilinear design is larger than that in the homogeneous design under a given heat flux condition. Originality/value – This study will help the design of the thermal protection system in reentry vehicles.